AVAILABILITY OF LOW-THRESHOLD Ca(2+) CURRENT IN RETINAL GANGLION CELLS - Lee, Sherwin C. (2003)
Spiking in central neurons depends on the availability of inward and outward currents activated by depolarization, and on the activation and priming of currents by hyperpolarization. Of these processes, priming by hyperpolarization is the least described. In the case of T-type Ca(2+) current availability, the interplay of hyperpolarization and depolarization has been studied most completely in expression systems, in part because of the difficulty of pharmacologically separating the Ca(2+) currents of native neurons. To facilitate understanding of this current under physiological conditions, we measured T-type current of isolated goldfish retinal ganglion cells with perforated-patch voltage clamp methods in solutions containing a normal extracellular Ca(2+) concentration. The voltage-sensitivities and rates of current activation, inactivation, deactivation, and recovery from inactivation were similar to those of expressed α1G (Ca(V)3.1) Ca(2+) channel clones, except that the rate of deactivation was significantly faster. We reproduced the amplitude and kinetics of measured T currents with a numerical simulation based on a kinetic model developed for an α1G Ca(2+) channel. Finally, we show that this model predicts the increase of T-type current made available between resting potential and spike threshold by repetitive hyperpolarizations presented at rates that are within the bandwidth of signals processed in situ by these neurons.